Pengaruh FED rate, inflasi, dan indeks NIKKEI 225 terhadap IHSG di Indonesia (2016-2017) - Joventus Partogi Silaen Joventus; Haryadi Haryadi; Emilia Emilia (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2019)
This study aims to analyze the influence and look at the Fed Rate, Inflation in Indonesia, and the NIKKEI 225 Index on the Composite Stock Price Index (JCI). The data used in this study is secondary data obtained from Bank Indonesia, Investing.com, library sources, journals, and other scientific articles. The analytical method used in this study is the multiple linear regression analysis method using the Ordinary Least Square (OLS) method. Data is processed using software using monthly data with the research period from January 2016-December 2017 sourced from the internet, scientific journals, and books. The results of this study indicate that partially the FED Rate variable has a negative effect on the JCI, Inflation has a negative effect on the JCI, and the NIKKEI 225 Index has no effect on the NIKKEI 225 Index. Meanwhile, simultaneously all variables affect the JCI. Keywords: Fed Rate, Inflation, NIKKEI 225 Index, IDX